AB0834 Efficacy and safety of hizentra(®) in patients with inflammatory myopathies after a switch from subcutaneous therapy. (23rd January 2014) - Moretti, R.; Paolini, L.; Gambini, S.; Gabrielli, A.; Danieli, M.G.
Abstract : Background: We have previously demonstrated the beneficial effect and the safety of subcutaneous immunoglobulin (SCIg) administration in active and refractory inflammatory myopathies. Hizentra (IgPro20; CSL Behring) is the first, 20% liquid preparation of human IgG specifically formulated for subcutaneous infusions. We here report on the switch to weekly subcutaneous infusions of Hizentra(®) in inflammatory myopathies. Objectives: We demontrate efficacy of the new formulation of subcutaneous immunoglobulins with quality of life improvement. Methods: Six severe idiopathic myositis (four with DM, two with PM), diagnosed according to the Bohan and Peter's criteria, were switched to weekly subcutaneous infusions of Hizentra(®) at doses equivalent to their previous subcutaneous treatment. A standardized protocol including the Medical Research Council (MRC) scale, the modified Rankin score, CK serum levels and daily prednisone dose, was used to evaluate patients and to assess disease activity, treatment response and quality of life. Results: All patients showed a favourable clinical response with normal CK serum levels and improvement in MRC and Rankin modified scores. No relapse of the disease occurred: patients reported a good tolerance to Hizentra (®). Local reactions were mild and self-limiting (only one patient showed swelling). No serious Hizentra(®)-related adverse events were reported whereas they pointed an improved quality of life. Patients' satisfaction was related to the shorter infusion times due to smaller infusion volumes, the easiness to handle the product and the possibility to store it a temperature up to 25°C. Conclusions: Hizentra is an advance in the field of immunoglobulin therapy, which might offer benefits for home therapy, even in patients with autoimmune diseases. Disclosure of Interest: None Declared